EFFECT OF VIGNA RADIATA SEED COAT FUNGI ON IN VITRO PHOSPHATE SOLUBILIZATION BY PHOSPHOBACTERIA - SINGH, GEETA; Singh, NEETA (Annals of Agricultural Research, 2014)
Aspergillus spp., Cephalosporium spp., Penicillium spp. and Trichoderma spp. were isolated from the spermosphere of Vigna radiata varieties. Effect of these fungi on commonly used phosphobioinoculant bacteria was assayed in vitro using tricalcium phosphate and Mussorie rock phosphate. Cephalosporium spp. and Penicillium spp. inhibited the phosphate solubilizing capacity of these phosphobacteria. However, Aspergillus spp. significantly improved the phosphate solubilizing ability of the tested phosphobacteria. Microflora on the seed surface play an important role in determining the performance of phosphobacteria. The negative effect of Cephalosporium spp. and Pencillium spp. was attributed to a heat labile fungal metabolite. This may be an antibiotic like substance.